Epidemiology and classification of scapular fractures: a detailed survey on a large sample of patients - Matteo Cantore, MD; Davide Manni, MD; Vittorio Candela, MD; Jacopo Preziosi Standoli, PT; Alessandro Are, MD; Stefano Gumina, PhD, MD (JSES International)
Background: Scapular fractures are rare, and few studies in the last 50 years have analyzed their epidemiology in depth. Most of these are dated, show a low sample size, or take into consideration only intra-articular fractures. Furthermore, in none of these studies recent classifications are used. Our aim was to retrospectively analyze a large number of patients to provide detailed epidemiological information about scapular fractures and to classify them with the latest classification system. Methods: Patients admitted for scapular fracture in two trauma centers over a 7-year period were enrolled. A retrospective review of the clinical and radiological data of all patients was performed by two of the authors. Information about age, gender, fracture side, traumatic mechanism, and associated fractures were collected, and all radiological images were classified according to the Arbeitsgemeinschaft für Osteosynthesefragen (AO)/Orthopaedic Trauma Association (OTA) classification system. Statistical analysis was performed. Results: A total of 243 patients (172 males and 71 females) with scapular fracture were admitted in the emergency department in a 7-year period. In this study scapular fractures represented 0.9% of all fractures and 6% of shoulder girdle fractures. Males were more often under 75 years of age whereas females were over 75 years. The right side was more involved than the left side. The association between traumatic mechanisms and sex was statistically significant. There were 142 low-energy fractures with 79 fractures involving men (56%) and 63 fractures involving women (44%); 101 injuries were the result of high-energy trauma with 93 cases involving men (92%) and 8 cases involving women (8%). The apophyses were involved in 26 cases (11%; 20 males and 6 females) and the scapular body was involved in 98 cases (40%; 83 males and 15 females). The glenoid fossa was fractured in 119 (49%) patients (69 fractures in men and 50 women). A significant association was found between gender and AO/OTA classification macro groups (P < .001). Females were more frequently affected by type F fractures whereas males more often presented type B fractures. Conclusions: Scapular fractures occur equally in both genders, although with different age distribution. Female patients are usually older and are mostly affected by low-energy traumas as a fall from standing height. Young males are more often subject to high-energy injuries that occur in road accidents, but with aging they become more prone to fragility fractures.